An Ayurvedic personalized prophylactic protocol in covid-19 (2020)
1. Background Severe acute respiratory syndrome-corona virus 2 (SARS-CoV-2), a novel β corona virus (CoVs) which is responsible for the pandemic pneumonia of 2020 is continuing its wrath worldwide [1]. The family of CoVs lately, have been the pathogens of emerging respiratory disease outbreaks in humans [2]. Scientists from various global health research organizations are desperately putting efforts into research on SARS-CoV-2 pathogenic mechanisms for developing prophylactic - therapeutic measures that would contain the transmission of this highly contagious virus and effectively reduce the number of casualties. Also, the pathological mechanism that is leading to severe stages of pneumonia is under scrutiny.